2015
DOI: 10.1007/978-94-017-9939-3_37
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the Reaction of Metakaolin in an Alkaline Environment by XPS, and Time- and Spatially-Resolved FTIR Spectroscopy

Abstract: The process of the dissolution of metakaolin in an alkaline environment remains incompletely understood; there are many mechanistic details which still require elucidation. Here, we apply X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) to provide new information regarding the bonding environments in the altered layer on the surface of a metakaolin particle in contact with different alkali hydroxide solutions (Li, Na and K as alkali cations, and concentrations ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This is consistent with the findings of previous studies in metakaolin-based geopolymers [12,22,28,30,33,34]. The decrease in wavenumber is indicative of angle and length changes of Si-O-Si and Si-O-Al bonds [28] and attributed to the substitution of SiO4 tetrahedra for AlO4 tetrahedra in the silicate network and to the occurrence of non-bridging oxygen sites [31,34]. Further, the band at 796 cm −1 was not observed in the spectra of the produced alkali-activated materials, in agreement with other studies [22,33], as a result of the change in Al coordination (from 6 to 4) and its participation in the silicate chains [34].…”
Section: Morphological Characterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the findings of previous studies in metakaolin-based geopolymers [12,22,28,30,33,34]. The decrease in wavenumber is indicative of angle and length changes of Si-O-Si and Si-O-Al bonds [28] and attributed to the substitution of SiO4 tetrahedra for AlO4 tetrahedra in the silicate network and to the occurrence of non-bridging oxygen sites [31,34]. Further, the band at 796 cm −1 was not observed in the spectra of the produced alkali-activated materials, in agreement with other studies [22,33], as a result of the change in Al coordination (from 6 to 4) and its participation in the silicate chains [34].…”
Section: Morphological Characterizationsupporting
confidence: 91%
“…The spectrum of WFG comprises typical bands for a glass [20,22] [12,22,30]. Most of the silicon sites are present in a 2D sheet consisting mainly of Q 4 (1Al) environments, thus Si-O-Si bonds are considered to contribute the most to this signal [31,32]. In this spectrum, the peak at 796 cm -1 can be attributed to Al (IV) -O and Si-O bending vibrations [22,33] or to the stretching vibrations of six-coordinated Al (VI) -O [34].…”
Section: Phase Characterizationmentioning
confidence: 99%
“…There have been a few experimental and theoretical studies on the dissolution of metakaolin during the geopolymerization process. Although a direct comparison with the results obtained here is not feasible due to the comparatively stronger alkaline conditions present in the geopolymer systems, the observation of preferential release of Al in metakaolin (Figure A) is in good agreement with the selective dissolution of Al reported in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 However, it should be noted that the decrease in dissolution rate at later stages may also originate from kinetic factors and not just thermodynamic factors, for example, the development of a protective altered layer on the particle surface 38,39 or an inhibitory effect of Al ions in the solution. [40][41][42][43] There have been a few experimental [44][45][46] and theoretical studies 47,48 on the dissolution of metakaolin during the geopolymerization process. Although a direct comparison with the results obtained here is not feasible due to the comparatively stronger alkaline conditions present in the geopolymer systems, the observation of preferential release of Al in metakaolin ( Figure 1A) is in good agreement with the selective dissolution of Al reported in these studies.…”
Section: Dissolution Kinetics For Calcined Kaolinitementioning
confidence: 99%
“…A number of studies have reported on their chemistry, microstructure development and engineering properties such as durability and resistance to fire and aggressive chemicals [4–6] . Different binders that are from natural sources such as clay, fired clay, pozzolans and industrial by‐products such as Fly ash and GGBS have been used in their manufacture [7–8] .…”
Section: Introductionmentioning
confidence: 99%